2010
DOI: 10.5194/acpd-10-25743-2010
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Charge induced stability of water droplets in subsaturated environment

Abstract: Atmospheric liquid and solid water particles are stabilized if they are coated with either negative or positive electric charge. The surface charge causes an increase of the partial pressure of water vapour close to the surface of each particle, effectively allowing the particles to remain in their condensed phase even if the environmental relative humidity drops below unity. The theory, briefly presented in this paper, predicts a zero parameter relation between surface charge density and water vapour p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…The observed polydispersity can be explained from the variation of the surface charge 21 , which dictates the size, the randomness of the Rayleigh effect and potential coalescences of the EWNS. However, as it was described in detail by Nielsen et al 22 the high surface charge reduces the evaporation by effectively increasing the surface energy/tension of the water droplets. This theory has been validated experimentally for micro-sized droplets 22 and for the EWNS in our previous publication 8 .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The observed polydispersity can be explained from the variation of the surface charge 21 , which dictates the size, the randomness of the Rayleigh effect and potential coalescences of the EWNS. However, as it was described in detail by Nielsen et al 22 the high surface charge reduces the evaporation by effectively increasing the surface energy/tension of the water droplets. This theory has been validated experimentally for micro-sized droplets 22 and for the EWNS in our previous publication 8 .…”
Section: Discussionmentioning
confidence: 90%
“…However, as it was described in detail by Nielsen et al 22 the high surface charge reduces the evaporation by effectively increasing the surface energy/tension of the water droplets. This theory has been validated experimentally for micro-sized droplets 22 and for the EWNS in our previous publication 8 . The overtime loss of charges might as well affect the size and contribute to the observed size distribution.…”
Section: Discussionmentioning
confidence: 90%
“…A droplet of nanoscale dimensions would be expected to evaporate in a few milliseconds in room air conditions (Robert E. Williamson & E. Dale Threadgill, 1974). However, Nielsen et al (Nielsen, Maus, Rzesanke, & Leisner, 2011) showed that the electric charge of water droplets retards their evaporation time significantly. As was shown in earlier studies with EWNS nanoparticles, their lifespan can reach up to several hours in indoor environmental conditions and their size does not change (Pyrgiotakis et al, 2016;Pyrgiotakis, McDevitt, Gao, et al, 2014).…”
Section: Physicochemical Characterization Of Iewnsmentioning
confidence: 99%
“…As a bipolar molecule, water shows strong electrical characteristics in the presence of surface charge and ambient atmospheric electric field. Charge and electric fields influence different microphysical processes like condensational or diffusional growth of water droplets (Lapshin et al, ; Nielsen et al, ), collision and coalescence process, and evaporation (Bhalwankar et al, ; Schlamp et al, , ), which in turn may influence the DSD inside cloud and can thereby modulate the DSD of precipitation at surface. For example, studies by Bhalwankar et al () and Bhalwankar and Kamra () have shown that the shape, growth, breakup, and evaporation characteristics of water drops are strongly influenced if the drops are charged or they are falling through electric fields.…”
Section: Introductionmentioning
confidence: 99%
“…Lapshin et al () proposed the enhanced condensational growth of polar molecules in highly ionized environments by the charge‐dipole mechanism. This charge‐dipole mechanism of induced growth of polar molecules can be attributed to the stabilization of water droplets in presence of surface charge in a subsaturated environment compared to uncharged droplet (Nielsen et al, ). These studies clearly suggest that although dynamics and microphysics of storm cloud may be the cause of initial electrical activity, the electrical forces within clouds in turn could modulate the microphysics thereby modulating the dynamics of the thunderstorm.…”
Section: Introductionmentioning
confidence: 99%